Synthesis and Bioactivity of N-(4-Chlorophenyl)-4-Methoxy-3-(Methylamino) Benzamide as a Potential Anti-HBV Agent - Cui AL; Sun WF; Zhong ZJ; Jin J; Xue ST; Wu S; Li YH; Li ZR (Dove Medical Press, 2020)
A-Long Cui,1,* Wen-Fang Sun,1,2,* Zhao-Jin Zhong,1 Jie Jin,1 Si-Tu Xue,1 Shuo Wu,1,2 Yu-Huan Li,1,2 Zhuo-Rong Li1 1Institute of Medicinal Biotechnology, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, People’s Republic of China; 2CAMS Key Laboratory of Antiviral Drug Research, Institute of Medicinal Biotechnology, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, People’s Republic of China*These authors contributed equally to this workCorrespondence: Si-Tu Xue; Shuo Wu Tel +86-10-63027185; +86-10-63010984Email xuesitu@imb.pumc.edu.cn; wushuoimb@126.comIntroduction: Hepatitis B virus (HBV) is a global health concern that can cause acute and chronic liver diseases. Thus, there is an urgent need to research novel anti-HBV agents. Our previous reports show that N-phenylbenzamide derivatives exert broad-spectrum antiviral effects against HIV-1, HCV, and EV71 by increasing intracellular levels of APOBEC3G (A3G). As A3G is capable of inhibiting the replication of HBV, we screened the N-phenylbenzamide derivatives against HBV.Methods: In this study, a new derivative, N-(4-chlorophenyl)-4-methoxy-3-(methylamino) benzamide (IMB-0523), was synthesized and its anti-HBV activity was evaluated in vitro and in vivo. The acute toxicity and pharmacokinetic profiles of IMB-0523 were also investigated.Results: Our results show that IMB-0523 has higher anti-HBV activity in both wild-type HBV (IC50: 1.99 μM) and drug-resistant HBV (IC50: 3.30 μM) than lamivudine (3TC, IC50: 7.37 μM in wild-type HBV, IC50: > 440 μM in drug-resistant HBV). The antiviral effect of IMB-0523 against HBV may be due to an increased level of intracellular A3G. IMB-0523 also showed low acute toxicity (LD50: 448 mg/kg) in mice and promising PK properties (AUC0-t: 7535.10± 2226.73 μg·h/L) in rats. Further, IMB-0523 showed potent anti-HBV activity in DHBV-infected ducks.Conclusion: Thus, IMB-0523 may be a potential anti-HBV agent with different mechanisms than current anti-HBV treatment options.Keywords: anti-HBV activity, APOBEC3G, hepatitis B virus, IMB-0523, PK, toxicity